Toward the Role of Language Teacher Confirmation and Stroke in EFL/ESL Students’ Motivation and Academic Engagement: A Theoretical Review - Gao, Yun (Frontiers in Psychology, 2021)
Following the recent special issue in the journal of Frontiers in Psychology, named “The Role of Teacher Interpersonal Variables in Students’ Academic Engagement, Success, and Motivation”, the present theoretical review is carried out to describe two prime instances of teacher interpersonal behaviors, namely teacher confirmation and stroke, their underlying frameworks, and their contributions to desirable student-related outcomes. In light of rhetorical-relational goal theory and the school of positive psychology, it is stipulated that language teacher confirmation and stroke are facilitators of EFL/ESL students’ level of motivation and academic engagement. Providing empirical evidence, I proved the argument regarding the pivotal role of language teacher confirmation and stroke in EFL/ESL contexts. Reviewing the available literature on the aforementioned variables, some pedagogical implications were suggested for teacher trainers, educational supervisors, and pre- and in-service language teachers. Finally, the limitations and drawbacks of the reviewed studies were identified and some avenues for further research were recommended, accordingly.